Exploring the Enigmatic Link between Religion and Anti‐Black Attitudes. Issue 9 (4th September 2015) - Howard, Simon; Sommers, Samuel R.
Abstract This review explores social psychological perspectives on the complex relationship between religion and anti‐Black prejudice in the United States. We examine the different ways in which religiosity has been conceptualized by behavioral scientists. We consider the methodological limitations of previous research, as well as how the advent of priming research introduces new empirical questions regarding religiosity and anti‐Black prejudice, such as whether activation of different religious conceptions (e.g., God versus religion) or priming via different types of stimuli (e.g., words versus images) produces different outcomes. Finally, we discuss the lack of diverse samples in the present literature and highlight the need for additional research with Black American respondents. Conclusions consider the real world implications of links between religion and anti‐Blackness for both White individuals (e.g., intergroup relations) and Black individuals (e.g., psychological functioning).